Effect of Surface Roughness of Al5052/CFRP Composites on Adhesion and Mechanical Properties - Lee, M.S.; Kim, S.J.; Lim, O.D.; Kang, C.G. (Asian Journal of Chemistry, 2014)
In this study, Al5052/CFRP composites were fabricated for an automobile component by compression molding process inside a U-channel mold. Al5052 sheet was treated by sand blasting with two different particle sizes. Accordingly, surface roughness (Ra) values of 4.25 and 1.85 μm were obtained for the treated Al5052 sheets. The effect of surface roughness of Al5052 sheets on the adhesion and mechanical properties of Al5052/CFRP composites have been evaluated. Shear lap test and 3-point bending test were conducted. Results showed that the shear load for the composite fabricated by using the treated Al5052 sheets with Ra value of 1.85 and 4.25 μm were three and five times higher than Ra value of 0.73 μm of the composite fabricated by using the untreated sheet. The bending stress of 200 MPa was obtained for the composite fabricated with untreated Al5052 sheets. The bending stress increased to 400MPa when the composite fabricated from treated sheets. However, the bending stress was not influenced by treating a condition through sand blasting.